Asuhan Keperawatan pada Klien Chronic Kidney Disease (CKD) dengan Hipervolemia di Ruang Melati RSUD Bangil - Arie Jefry Ka’arayeno; Maria Noviana Kii; Errcik Endra Cita (LPPM STIKES Guna Bangsa Yogyakarta, 2025)
Hypervolemia worsens the condition of clients with chronic kidney disease, kidney function will be gradually disrupted. Handling hypervolemia is one of the focuses of nursing care in patients with kidney failure to overcome fluid accumulation. The purpose of this study was to explore nursing actions using outcome standards and nursing interventions to overcome hypervolemia in patients with chronic kidney failure. The methodology of this study is qualitative with a case study approach including direct observation, physical examination, interviews, and analysis of laboratory examination findings as a series in a case study approach. The analysis uses descriptive analysis based on the concept of SDKI, SLKI and SIKI theories. The number of clients was 3 people with hypervolemia nursing problems. The signs and symptoms found in the three clients were orthopnea, dyspnea, extremity edema, increased JVP, positive hepatojugular reflex, oliguria, decreased Hb/Ht and increased blood pressure. Based on the evaluation results, orthopnea and dyspnea decreased, edema decreased sufficiently, urine output increased sufficiently, JVP improved sufficiently, blood pressure improved sufficiently and Hb/Ht improved sufficiently so that it was concluded that the hypervolemia nursing problem had been partially resolved. Various interventions are performed including monitoring hemodynamic status, fluid intake and output, signs of hemoconcentration, raising the head of the bed 30 to 40 degrees, administering oxygen, and providing instructions for limiting fluid intake. Most clients show improvement in symptoms but still require further monitoring.